PENGARUH PENGELOLAAN KELAS DAN PENGGUNAAN MEDIA PEMBELAJARAN OLEH GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK SEKOLAH MENENGAH ATAS NEGERI KOTA MALANG - Intan Mu’izzah Riyanto; Agus Timan; Djum Djum Noor Benty; Intan Mu’izzah Riyanto; Agus Timan (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: This study aims to describe the level of classroom management, the use of learningmedia, and learning motivation, as well as the effect of classroom management andthe use of learning media on students' learning motivation. The method in thisstudy uses a quantitative approach with multiple linear regression analysis models,with 360 students as respondents. Collecting data in this study using aquestionnaire distributed via Google Form. The results of this study indicate thatthe level of class management, the use of learning media in the quite effectivecategory and the learning motivation in the moderate category, and there is asignificant influence between class management and the use of learning media onthe learning motivation of students.